On the Structural Dimension of Competitive Strategy - Serguei Kaniovski; Michael Peneder (Austrian Institute of Economic Research (WIFO), 2001)
This paper aims at establishing the existence of systematic differences in the nature of competitive strategies available to individual firms across industries. By means of qualitative content analysis, we extracted a matrix of 76 industries times 12 strategies reported as being characteristic in a series of monographs. Subsequent tests for the statistical significance of observed differences in the typical strategy portfolio show an evident link to an industry's general reliance on intangible investments, human resources, and inputs from external services.
Keywords: L1; L6; O3; 330; Corporate strategy; Industrial structure; technological regimes; intangible assets; human resources; external services; Strategisches Management; Wettbewerbsstrategie; Wirtschaftsstruktur; Industriestruktur; Immaterielle Werte; Humanressourcen; Evolutionsökonomik; Theorie